The clinical characteristics of fungal keratitis in eyes after Descemet’s stripping and automated endothelial keratoplasty - Araki-Sasaki K (Dove Medical Press, 2014)
Kaoru Araki-Sasaki,1,2 Atsuko Fukumoto,1 Yasuhiro Osakabe,3 Hideya Kimura,1 Shinichiro Kuroda1 1Nagata Eye Clinic, Nara, Japan; 2Department of Ophthalmology, Japan Community Health Care Organization, Hoshigaoka Medical Center, Osaka, Japan; 3Department of Molecular Pathology, Tokyo Medical University, Tokyo, Japan Abstract: The purpose of this study was to describe the clinical characteristics of fungal keratitis caused by Candida albicans in an eye after Descemet stripping automated endothelial keratoplasty (DSAEK). A 72-year-old male with a history of three trabeculectomies, cataract surgery, and two DSAEK procedures developed a corneal ulcer in his right eye two years after his last DSAEK. Fungal keratitis was most likely related to the immunosuppressive conditions that occurred due to the previous operations, the continuous use of steroid eye drops, and the use of disposable soft contact lenses. A smear and culture from the ulcer detected Candida albicans. Slit-lamp examination showed the characteristic feature was the presence of interface infiltrates located between the host and the graft cornea and in the enlarged area around the ulcer. Two weeks after intense antimycotic treatments with voriconazole, miconazole, and natamycin, perforation of the cornea occurred and further therapeutic penetrating keratoplasty was required. Histological analysis revealed an accumulation of infiltrated cells and fibrotic tissue. The poor prognosis for fungal keratitis that occurs in eyes after undergoing DSAEK may be related to the rapid expansion of inflammatory cells through the interface between the host and the graft. In eyes that develop fungal keratitis after DSAEK, special attention should be paid to the possibility that perforation could occur in these patients. Keywords: DSAEK, Candida albicans, fungal keratitis, keratomycosis, post-operative infection